2016
DOI: 10.4049/jimmunol.1502462
|View full text |Cite
|
Sign up to set email alerts
|

LLT1 and CD161 Expression in Human Germinal Centers Promotes B Cell Activation and CXCR4 Downregulation

Abstract: Germinal centers (GC) are microanatomical structures critical for the development of high-affinity antibodies and B-cell memory. They are organised into two zones, light and dark, with coordinated roles, controlled by local signalling. The innate Lectin-like transcript 1 (LLT1) is known to be expressed on B-cells, but its functional role in the GC reaction has not been explored. Here we report high expression of LLT1 on GC-associated B-cells, early plasmablasts and GC-derived lymphomas. LLT1 expression was rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 72 publications
3
46
1
Order By: Relevance
“…We screened a wide variety of human cell types and tissues using our novel monoclonal antibody, clone 2H7, and described LLT1 expression in circulating B cells and monocytes. The presence of LLT1 could also be observed in B cells in tonsils, as previously described 6, 9, 21 , but not in Kupffer cells in the liver or alveolar macrophages in the lung. Furthermore, LLT1 could be detected in several healthy human tissues, but it was remarkably prevalent in immune-privileged sites, such as brain, placenta and testes.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…We screened a wide variety of human cell types and tissues using our novel monoclonal antibody, clone 2H7, and described LLT1 expression in circulating B cells and monocytes. The presence of LLT1 could also be observed in B cells in tonsils, as previously described 6, 9, 21 , but not in Kupffer cells in the liver or alveolar macrophages in the lung. Furthermore, LLT1 could be detected in several healthy human tissues, but it was remarkably prevalent in immune-privileged sites, such as brain, placenta and testes.…”
Section: Introductionsupporting
confidence: 82%
“…We and others have shown the expression of LLT1 in tissue resident germinal centre B cells 6, 9 . We demonstrated that the 2H7 mAb recognises LLT1 on germinal centre B cells, both immunohistologically and by flow cytometry ( Figure 1C) 6 . Thus, the 2H7 mAb is a good tool for studying the distribution of LLT1 in tissue through immunohistochemical staining.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Multiple therapeutic possibilities involving CXCR4 have been attempted including monoclonal antibodies [139], the pan-PI3K inhibitor BKM120 [146] and crosslinking of LLT1 [147]. …”
Section: Follicular Lymphomamentioning
confidence: 99%